MOBILE APPLICATION – GROUP MESSAGING APPLICATION FOR PROJECT MANAGEMENT - Mohamad Shiham, Nasuha Sofwani (IRC, 2019)
The increasing demand for convenient applications as led to a growing technology usage that can make every day work easier. As a result, it leads to an idea to create a system for a better communication of project management without leaving any committee in confusion. This system is designed to help people to conduct a better distribution of information in a fast and easy way. The chat system will be available in both Android and IOS system in order to ensure the efficiency of the application. The project produces is risk free and more compatible to be use in a project management to organized, transfer and save the important information of the event. It is made for general population of the nation living the world over and need to transfer the information in more efficient ways. The project is inspired by Knowledge Management System which is providing the right ways of acquiring, organizing and transferring knowledge to the all people by using right mechanism. By using the right tools and techniques, all the information can be delivered effectively and can be applied efficiently. Knowledge are classified in two category which is tacit and explicit. Each category has different ways of transferring the information. Based on this project, we are using the method of transferring information of tacit which is directly from sender and change it to explicit which are public to the users. Some information in the project also can be explicit to explicit as it was already available in other sources. Basically, this project helps the user to save important details in project management so no information are missing and all important details are organized in one places according to the category set. Methodology that applied when build this application is using prototype system. This application is based on Android platform as a framework. It also used Firebase for the database. The development of this system able to help user on creating a group chat specific for the project management, adding category needed, adding more members in the group, classified certain knowledge in their category, create own account for the chat system and able to search for the information.